PEMANFAATAN MOBILE COMMERCE GUNA MENINGKATKAN PENJUALAN UMKM NARESCRAFT DI DESA TULUNG AGUNG - Wulandari Wulandari; Rosa Afriliani (STMIK Pringsewu, 2021)
Narescraft UMKM is a business that produces various kinds of handicraft products made of talikur and acrylic. This UMKM is located in Tulung Agung Village, Kec. Gadingrejo, Kab. Pringsewu. This UMKM produces items such as bags made of talikur, decorative flowers from acrylic, tissue boxes and aqua baskets, and many others. This research discusses the use of m-commerce at Narecraft UMKM to increase product sales. One form of constraint experienced by Narescraft UMKM is product marketing that has not been widespread due to a lack of knowledge about current technological developments. One of the benefits of this research is to make it easier. consumers to get goods according to what they want easily. This research designs a website as a means of promotion or sale of products from UMKM so that products from UMKM can be widely known by the outside community. Researchers design a website using mobile software. a free application/software that can make the best free responsive website designs for Windows, Mac, and Android. Researchers use the implementation of m-commerce with websites on UMKM so that they can help reduce costs and can convey detailed information. This research hopes to help increase sales of these handicraft products.